Correction to: A new multiple trauma model of the mouse - Stefanie Fitschen-Oestern; Sebastian Lippross; Tim Klueter; Matthias Weuster; Deike Varoga; Mersedeh Tohidnezhad; Thomas Pufe; Stefan Rose-John; Hagen Andruszkow; Frank Hildebrand; Nadine Steubesand; Andreas Seekamp; et al. (BMC Musculoskeletal Disorders, 2019)
After publication of the original article [1], it was noticed that the following corrections needed to be implemented.